2020
DOI: 10.1038/s41598-020-67934-2
|View full text |Cite
|
Sign up to set email alerts
|

Serum GFAP in multiple sclerosis: correlation with disease type and MRI markers of disease severity

Abstract: Neurofilament light chain (NfL) has been demonstrated to correlate with multiple sclerosis disease severity as well as treatment response. nevertheless, additional serum biomarkers are still needed to better differentiate disease activity from disease progression. The aim of our study was to assess serum glial fibrillary acid protein (s-GFAP) and neurofilament light chain (s-NfL) in a cohort of 129 multiple sclerosis (MS) patients. Eighteen primary progressive multiple sclerosis (PPMS) and 111 relapsing remitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
2
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(81 citation statements)
references
References 21 publications
6
69
2
4
Order By: Relevance
“…A cohort study by Xavier Ayrignac and colleagues evaluated sNFL and s-GFAP levels in 129 MS patients (Ayrignac et al, 2020[ 5 ]). 111 out of 129 patients had PPMS while the other 18 had RRMS.…”
Section: Neurofilament Light Chain As a Biomarker For Diagnosis Of Multiple Sclerosismentioning
confidence: 99%
See 2 more Smart Citations
“…A cohort study by Xavier Ayrignac and colleagues evaluated sNFL and s-GFAP levels in 129 MS patients (Ayrignac et al, 2020[ 5 ]). 111 out of 129 patients had PPMS while the other 18 had RRMS.…”
Section: Neurofilament Light Chain As a Biomarker For Diagnosis Of Multiple Sclerosismentioning
confidence: 99%
“…However, analysis revealed that the s-GFAP measurements were significantly different. Their results showed that the s-GFAP levels correlated with the white matter lesion load by MRI, but had an inverse correlation with white matter and grey matter volume (Ayrignac et al, 2020[ 5 ]).…”
Section: Neurofilament Light Chain As a Biomarker For Diagnosis Of Multiple Sclerosismentioning
confidence: 99%
See 1 more Smart Citation
“…Pasquali et al reported that the plasmatic levels of proinflammatory cytokines, both IFN-γ and IL-17, are higher in RRMS compared to SPMS patients, while the level of transforming growth factor-β (TGF-β), a molecule with immunosuppressant activity, was much lower in RRMS in comparison to SPMS [ 35 ]. Another group of active molecules indicated in the literature are light neurofilaments (NFL) and glial fibrillary acid protein (GFAP), a marker of astrocyte damage and astrogliosis, in serum [ 36 , 37 ]. Högel et al claimed that GFAP and NFL levels in serum are higher in patients with SPMS than RRMS, as well as correlate with a higher EDSS parameter [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…Högel et al claimed that GFAP and NFL levels in serum are higher in patients with SPMS than RRMS, as well as correlate with a higher EDSS parameter [ 38 ]. Whereas Ayrignac et al demonstrated higher levels of both NFL and GFAP in serum from PPMS compared to RRMS, indicating that they might be markers of the disease progression [ 37 ]. Based on the above studies, we consider NFL and GFAP as potential progressive MS and RRMS distinguishing biomarkers.…”
Section: Introductionmentioning
confidence: 99%